(untitled) (Journal of Kidney Cancer, 2026)
To evaluate whether the length of positive surgical margin carries a risk for recurrence, data of patients that underwent partial nephrectomy (PN) from six centers were evaluated. Fifty-three patints with positive surgical margins (PSMs) (the PSM group) and 438 patients with negative surgical margin (the NSM group) were included in the present study. Pathologic reevaluations were performed, and surgical margins were measured in micrometers. The number of positive margin areas, and the length of the maximum and total positive margins were evaluated. Data were analyzed using SPSS 27 package program. A p-value less than 0.001 was considered statistically significant. Local recurrence occured in 16.98% of patients in the PSM group and 4.24% of patients in the NSM group. (p<0.001). Patients with PSM were at fourfold increased risk for recurrence. Age, gender, tumor location, tumor side and size, and fuhrman grade were not associated with local recurrence of the tumor (p>0.01). However, positive surgical margin was an important risk factor for local recurrence (p<0.01). No relationship was found between pos-itive margin length and local recurrence (p=0.044). Logistic regression analysis did not identify any parameters associated with local recurrence. The presence of a PSM was significantly associated with an increased risk of local recurrence following PN. The number of positive margin foci and total or maximum length of margin involvement were not associated with recurrence. These findings suggest that it is the presence of PSM, rather than its extent, that may be the primary factor influencing oncological risk.